LIMOCE: Live Migration of Containers in the Edge - Das, Rohit; Sidhanta, Subhajit (2021 IEEE/ACM 21st International Symposium on Cluster, Cloud and Internet Computing (CCGrid), 2021)
Being comprised of resource-constrained edge devices, live migration is a necessary feature in edge clusters for migrating state of an entire machine in case of machine failures and network partitions without disrupting continued availability of services. While most of the prior work in this area has provided solutions for live migration on clusters comprised of resource-rich servers or fog servers with high computing power, there is a general lack of research in live migration on the low-end ARM devices comprised in edge clusters. To that end, we propose a lightweight algorithm for performing live migration on resource constrained edge clusters. We provide an open source implementation of the above algorithm for migrating containers in Linux. We demonstrate that our algorithm outperforms state-of-the-art live migration algorithms on resource constrained edge clusters with network partitions and device failures.